Prevalence and Predictors of Atrial Fibrillation among Patients Undergoing Bariatric Surgery - Shoemaker, M. Benjamin (2014)
INTRODUCTION/PURPOSE: While AF is a disease of the elderly, it can occur earlier in the presence of risk factors such as obesity. Bariatric surgery patients are significantly younger and more obese than previously described populations with AF. Therefore, it remains to be determined whether current estimates of the prevalence and predictors for AF remain true in the bariatric surgery population. MATERIALS AND METHODS: We performed a cross-sectional analysis of 1341 consecutive patients who underwent bariatric surgery from 1/2008 to 10/2012. Baseline characteristics were compared between patients with and without AF. For additional comparison, 176 patients with AF and body mass index (BMI) >40 kg/m(2) were identified from the Vanderbilt AF Registry. A multivariable logistic regression was performed to identify predictors of AF within the bariatric surgery cohort. RESULTS: The prevalence of AF in the bariatric surgery cohort was 1.9% (25/1341). Patients with AF were older (median 56 years (Interquartile range [52-64) vs.46 [38-56] years, p<0.001), were more often male (48% vs. 23%, p=0.004), had more comorbidities, but had no difference in BMI (50 kg/m(2) [44-58] vs. 48 [43-54], p=0.4). In multivariable analysis, the odds of AF increased 2.2-fold by age per decade (95% CI: 1.4-3.5, p<0.001) and 2.4-fold by male gender (1.1-5.4, p=0.03) when adjusted for BMI. BMI was not independently associated with AF (OR 1.15 [95% CI: 0.98-1.41], p=0.09). CONCLUSIONS: The prevalence of AF is 1.9% among patients undergoing bariatric surgery. Risk of AF was found to increase with age and male gender, but not with higher BMI.